Risk factors for low birth weight infants in East Nusa Tenggara - Khrispina Owa; I Wayan Gede Artawan Eka Putra; I Gusti Ayu Trisna Windiani (Universitas Udayana, 2017)
Background and purpose: Low birth weight (LBW) is a major cause of neonatal and infant mortality. The Indonesian Demographic and Health Survey indicated that neonatal mortality rate in East Nusa Tenggara was 26 per 1000 live births, 15% of which were caused by low birth weight. This study aims to understand the relationship between age of mother, birth spacing, chronic energy deficiency, presence of concomitant diseases, employment status, anemia, quality of antenatal care and traditional dietary restrictions on the incidence of LBW in Ende District, East Nusa Tenggara. Methods: A case control study was conducted at Ende District in 2015, with a total of 156 respondents. Cases were mothers giving birth to LBW infant (<2500 gram) and controls were mothers giving birth to normal weight infant (≥2500 gram). Case and control ratio was 1:1. Data were obtained from antenatal care records and interviews. Data were analysed using bivariate analysis and multivariate with logistic regression. Results: This study found that risk factors of LBW include age of mother <20 or ≥35 years (AOR=6.8; 95%CI: 1.87-25.0), traditional dietary restrictions (AOR=6.7; 95%CI: 1.71-26.8), birth spacing <2 years (AOR=6.5; 95%CI: 1.78-24.2), chronic energy deficiency (AOR=5.3; 95%CI: 1.38-21.0), being employe (AOR=4.6; 95%CI: 1.44-14.9), anemia (AOR=4.2; 95%CI: 1.37-13.1), malaria infection (AOR=3.9; 95%CI: 1.21-12.7) and low quality of antenatal care (AOR=3.5; 95%CI: 1.11-11.3). Conclusions: Age of mother <20 or ≥35 years, traditional dietary restrictions, birth spacing <2 years, chronic energy deficiency, maternal occupation, anemia, malaria infection and low quality of antenatal care are risk factors for LBW in the District of Ende.